Foreword 125-1 - In memory of Maurizio Gaetani (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
The first issue of volume 125 (2019) of Rivista Italiana di Paleontologia e Stratigrafia is dedicated to the memory of Maurizio Gaetani (1940-2017), world-renowned Professor of Geology and Stratigraphy at the University of Milan, to honour his fruitful life of research and his grandeur as a man, a friend, a mentor and an Editor of this journal.